Explaining the Communication Pattern of Attention to Health and Humor in the Work Environment with the Mediating Role of Sports Activities in Elementary School Teachers - Faraziani, Fateh (Health Nexus, 2024)
This research aims to elucidate the relationship between health awareness and humor in the work environment, focusing on the mediating role of sports activities among elementary school teachers. A correlational survey method was employed. The study population comprised all male and female elementary school teachers in Sahne City, totaling 289 individuals (126 men and 163 women). A sample of 182 participants was selected using the Krejcie and Morgan table. Research instruments included healthcare questionnaires (Sijtsama and Beck, 2009), humor measurement in the work environment (Maja et al., 2009), and self-reports on sports activities. Data analysis was conducted using SPSS 22 and SmartPLS 3 software, utilizing descriptive statistics, the Kolmogorov-Smirnov test, and structural equation modeling via the partial least squares method. Results indicated that teachers' attention to health and sense of humor are favorable. Teachers' sports activities ranged from low to moderate levels. Increased health awareness among elementary teachers correlated with higher levels of humor. However, sports activities did not significantly affect teachers' humor levels or mediate the relationship between health awareness and humor.The findings suggest that the mediating variable (sports activities) did not reach the desired level to impact teachers' humor significantly. Similarly, health awareness did not considerably influence humor through sports activity mediation. It is recommended that specialized classes for physical and mental sports activities (e.g., yoga, meditation) be planned and implemented for teachers.